Are current accountability frameworks appropriate for degree apprenticeships?. Issue 4 (14th November 2016) - Lambert, Steve
Abstract : Purpose: In 2015 the Conservative led government announced their plan to increase the number of young people participating in apprenticeship to three million by 2020. As part of this plan there is to be an expansion of the number of degree-level apprenticeships, with the government suggesting that these should be seen as a real alternative to university. Despite the government's propaganda of an alternative to university, higher education institutions have a pivotal role to play in both the development and delivery of degree-level apprenticeships. However, the accountability for the success of degree-level apprenticeships remains unclear. The paper aims to discuss these issues. Design/methodology/approach: The paper provides an analysis of current notions of outcome-based accountability contextualised through the degree apprenticeship programme. Findings: The paper illustrates that outcome-based accountability frameworks do little to support the delivery of degree-level apprenticeships. Instead there needs to be a shift to a holistic approach to accountability where student success form just one element of an accountability framework. It concludes that current accountability frameworks may result in an unnecessary confusion around the roles and responsibilities of individual actors associated with degree apprenticeship delivery resulting in a missed opportunity to maximise the value arising from the tri-partite delivery relationship. Originality/value: This paper provides an original perspective involving accountability associated with degree apprenticeship programmes in the UK.